Digitalization impact factorial analysis on the consolidation prospects of urban communities - A. A. Garmashev; P. K. Velikikh; E. V. Velikikh (Цифровая социология)
The article deals with the influence problem of digitalization processes on the prospects of urban communities’ consolidation, which is implemented through a system of multi-level factors. The opinions of modern researchers and practitioners are studied on the introduction impact of digital technologies on the process of social consolidation. The article is based on the study results of expert surveys and focus group interviews, and ambivalent assessments of participants were obtained regarding the digital transformation of society. The paper presents the expert assessment results of the factors’ importance of urban communities’ consolidation and the influence of the second level’s digitalization factor on the prospects of urban communities’ consolidation. On the basis of these data, the following conclusions are formulated: in cases where digital transformation contributes to the improvement of social interactions, it will stimulate consolidation; reflection on the negative consequences of the digital technologies’ introduction, dehumanization of social reality as a result of its hybridization may prompt citizens to consolidate.